Pengaruh Lingkar Kepala Janin dan Berat Badan Lahir terhadap Kejadian Ruptur Perineum di Puskesmas Malakopa - Hasanalita Hasanalita; Epi Satria; Afrah Diba Faisal (Poltekkes Kemenkes Padang, 2024)
In 2022, data from the Indonesian Ministry of Health and the Mentawai Islands Health Service, the number of maternal deaths shows 7,389 deaths in Indonesia. In West Sumatra there were 193 cases, and in the Mentawai Islands there were 382 people. Perineal rupture causes infection in the suture wound and can spread to the bladder and birth canal, resulting in bladder infections, infections in the birth canal and bleeding. The aim of this study was to examine the influence of the baby's head circumference and birth weight on the incidence of perineal rupture in mothers giving birth at the Malakopa Community Health Center. Cross Sectional design analytical research type. The population and sample in this study were all women giving birth at the Malakopa Community Health Center with a total population of 41 samples carried out in February 2024. Data collection used medical records. The data were analyzed using frequency distribution and Chi-Square statistical tests. The results of the study showed that the weight of normal babies who experienced perineal rupture was 34.7%, while the weight of abnormal babies who experienced perineal rupture was 73.3%, with a value of p = 0.017 (pvalue < 0.05). ). The head circumference of normal babies in mothers who experienced perineal rupture was 36%, while the head circumference of babies who experienced perineal rupture was 68.8%, whereas the p value = 0.041 (pvalue < 0.05). It was concluded that there was an influence of fetal head circumference and birth weight on the incidence of perineal rupture. It is hoped that this research can become a reference for other researchers evaluating Puskesmas.